Image password lock system by tracing position information of the pupil - Lin, Chern-Sheng; Lay, Yun-Long; Lin, Chi-Chin; Chiu, Chuang-Chien; Yeh, Mau-Shiun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, a new method for an improved image password lock system by tracing position information of the pupil is described. The present technology relates to an efficient auto-detecting function, and in particular, to an image password lock system, which can provide the benefits of a novel password input mode without any contact. In this system, a PC camera device detects a movable target object to read a dynamic eye image data. Moreover, the dynamic eye image data has a predetermined shooting range set to be a whole-region image, and the whole-region image has a central region and a plurality of specific password regions. A target eye image is displayed by a display device, and then processed by an image processing device, thereby calculating a center coordinate point of the target eye image in the dynamic image data, compiling a password constituted by a movement position of the target object image, displaying the password, and validating the password. Therefore, the benefits of a novel password input mode without any contact, an efficient anti-theft function, are provided.
Optica Applicata, Vol. 39, 2009, nr 1, s. 149-160
Keywords: optyka; image password lock system; tracing position information, pupil